Association between Serum Uric Acid and Non-Alcoholic Fatty Liver Disease according to Different Menstrual Status Groups - Yanru Chen; Qiuping Huang; Ping Ai; Huamin Liu; Xueyu Chen; Xizhu Xu; Guoyong Ding; Yuejin Li; Xia Feng; Xiaohui Wang; Long Ji; Dong Li; et al. (Canadian Journal of Gastroenterology and Hepatology)
Objective. The present study aimed to explore the association between SUA and NAFLD in women with different menstrual statuses. Methods. A total of 6043 women were selected from the Jidong and Kailuan communities for inclusion in the present study. The SUA levels of participants were divided into quartiles. NAFLD was determined by abdominal ultrasonography. Data from laboratory tests and clinical examination were collected, and basic information was obtained from standardized questionnaires. The menstrual status was stratified into menstrual period, menopause transition period, and postmenopause. Multivariate logistic regression models were used to determine the relationship between menstrual status, SUA, and NAFLD. Results. The levels of SUA in subjects with NAFLD in the menstrual period, menopause transition period, and postmenopause were 268.0 ± 71.1, 265.6 ± 67.8, and 286.7 ± 75.8 (mmol/L), respectively, and were higher than those in subjects without NAFLD. The adjusted odds ratios (ORs) with 95% confidence interval (CI) for NAFLD among participants in the menopause transition period and postmenopausal period were 1.10 (0.89–1.37) and 1.28 (1.04–1.58), respectively, compared with the menstrual period women. Compared to the lowest quartile of SUA, the adjusted ORs with 95% CI of the highest quartile for NAFLD were 2.24 (1.69–2.99) for females in the menstrual period, 1.92 (1.10–3.37) for females in the menopause transition period, and 1.47 (1.06–2.03) for females in postmenopause. Conclusions. Menstrual status was significantly correlated with NAFLD. High levels of SUA were associated with NAFLD in females during the three menstrual periods.